LOW-CARBON TRANSFORMATION IN FERROUS METALLURGY - Mamatmuminova Z.I. (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
Low carbon economy (LCE), or “green economy”, characterized by low consumption of fossil fuels and the associated low environmental impact. The transition to a low-carbon economy is achieved through the implementation of energy efficiency, climate security and environmental security policies. At the same time, the synergistic effect of energy saving is activated